Parenting Patterns in Orphanages in Fostering Morals in Early Childhood - Fiki Jauharoh Huriyah; Lidia Humaiora (Socrates: Journal of Education, Philosophy and Psychology, 2025)
The abstract of the research titled "Foster Care Patterns in Shaping the Moral Development of Early Childhood" aims to identify the parenting patterns implemented in orphanages and the inhibiting and supporting factors in the moral development of children. This study employs a qualitative descriptive method with a sample of 45 children and 6 caregivers. The findings indicate that the parenting patterns consist of three aspects: the religious aspect (such as performing the five daily prayers), the social aspect (interaction of children within the orphanage and the community), and the individual aspect (apologizing when making mistakes). The inhibiting factors in the moral development of children include the varying backgrounds of the children, lack of attention, and environmental influences. Meanwhile, the supporting factors include children's motivation, community support, and assistance from caregivers. This research is expected to provide a clear understanding of the role of orphanages in the moral development of children